A self-consistent model for temperature and current distribution in abrupt heterojunction bipolar transistors. - Anwar, A.F.M (IEEE Transactions on electron devices)
The thermal behavior of abrupt heterojunction bipolar transistors (HBTs) has been studied by coupling the thermionic-field-emission injection mechanism at the emitter-base heterojunction with the thermal-electric feedback phenomenon. The exact quantum mechanical injection mechanism rather than the semiclassical WKB approximation is used in the present calculation to self-consistently calculate the thermionic and tunneling components of current. Moreover, the total current and temperature are self-consistently evaluated by testing the convergence on both current and temperature. The calculation shows correctly that the degree of the partitioning between the thermionic and tunneling components are bias- as well as temperature-dependent. It is shown that even a single emitter finger can have a highly nonuniform temperature and current distribution across it, leading to the current collapse phenomenon. At high power levels, this may give rise to a current collapse phenomenon similar to that observed for the multifinger HBTs.